A lattice Boltzmann modeling and analysis of the thermal convection in a lithium-ion battery. (15th May 2019) - Jiang, Jibing; Li, Dinggen; Dou, Ruzhen
Abstract: Thermal convection is a critical problem in the design of thermal management system, and is widely encountered in electric and hybrid electric vehicles. In the present work, the lattice Boltzmann method is adopted to investigate the thermal convection in the LiN i x C o y M n z O 2 (NCM) lithium-ion battery. The numerical results reveal that the thermal convection model considered in the current study can clearly depict the temperature evolution in the case of the thermal runaway. Additionally, it is found that as the adiabatic boundary condition is adopted, the maximum temperature inside the battery can reach 320°C at 240s, which in turn affects the surrounding batteries. To prevent the thermal runaway propagation in such a case, we also analyzed the forced convective heat transfer in this situation, and the numerical results indicate that thermal runaway can be effectively decreased if the value of the surface heat transfer coefficient for battery cell increases up to 200Wm −2 K −1 . Moreover, it is noted that when the temperature inside the battery reaches 110°C, the subsequent temperature distributions inside the battery have little influence on the surrounding batteries, which suggests that the thermal management of battery pack in both normal charge and discharge process should be considered.